Respostas
respondido por:
1
G) -3x = 10 . (-1)
3x = -10
x=
x= - 3,333...
H) -5x = -12 . (-1)
5x = 12
x=
x= 2,4
M) 2x - 5 = x+1
2x - x = 1 +5
x= 6
3x = -10
x=
x= - 3,333...
H) -5x = -12 . (-1)
5x = 12
x=
x= 2,4
M) 2x - 5 = x+1
2x - x = 1 +5
x= 6
lovatoxxx:
Muito obrigada! você é uma gênia!
respondido por:
0
Resposta:
G) -3x = 10 . (-1)
3x = -10
x=
x= - 3,333...
H) -5x = -12 . (-1)
5x = 12
x=
x= 2,4
M) 2x - 5 = x+1
2x - x = 1 +5
x= 6
Explicação passo-a-passo:
Espero ter ajudado, deu um trabalhão para eu fazÊ ;_;
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás